β2-Microglobulin and Neutrophil Gelatinase-Associated Lipocalin, Potential Novel Urine Biomarkers in Periodontitis: A Cross-Sectional Study in Japanese - Mayuka Nakajima; Michihiro Hosojima; Koichi Tabeta; Sayuri Miyauchi; Miki Yamada-Hara; Naoki Takahashi; Haruna Miyazawa; Yumi Matsuda-Matsukawa; Keisuke Sato; Noriko Sugita; Yasutaka Komatsu; Tomomi Ishikawa; et al. (International Journal of Dentistry)
Objectives. Several serum biomarkers have been reported to increase in periodontitis patients as possible mediators linking periodontal inflammation to systemic diseases. However, the relationship between periodontitis and urine biomarkers is still unclear. The aim of this cross-sectional study was to investigate potential urine biomarkers of periodontitis in a Japanese population. Materials and Methods. This study included 108 male subjects, and microbiological and clinical parameters were evaluated as a periodontitis marker. The correlation between nine urine biomarkers (typically used to diagnose kidney disease) and periodontal parameters was analyzed. Based on the findings, β2-microglobulin (β2-MG) and neutrophil gelatinase-associated lipocalin (NGAL) were selected for comparison and multivariate regression analysis, and the Kruskal–Wallis test followed by Bonferroni correction was used to identify differences in their concentrations between the three periodontitis groups (severe, moderate, and no/mild periodontitis). Results. β2-MG and NGAL exhibited a significant correlation with clinical parameters of periodontitis. The prevalence of clinical parameters such as bleeding on probing and number of sites with probing depth (PD) ≥ 6 mm were greater in the β2-MG high group (≥300 μg/g creatinine) than in the normal group (P=0.017 and 0.019, respectively). Multivariate regression analysis indicated that the number of sites with PD ≥ 6 mm was independently associated with urine β2-MG. Moreover, the number of sites with the clinical attachment level (CAL) ≥ 6 mm was greater in the NGAL high group (highest quartile) (P=0.041). Multivariate regression analysis showed that the number of sites with CAL ≥ 6 mm was associated independently with urine NGAL. Finally, β2-MG was significantly higher in the severe periodontitis subjects compared to the no/mild periodontitis subjects. Conclusion. The significant association between urine β2-MG or NGAL and periodontitis was revealed. These biomarkers can potentially be used to screen for or diagnose periodontitis. This trial is registered with the UMIN Clinical Trials Registry UMIN000013485.